2015
DOI: 10.1088/0004-637x/808/1/70
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino-Driven Turbulent Convection and Standing Accretion Shock Instability in Three-Dimensional Core-Collapse Supernovae

Abstract: We conduct a series of numerical experiments into the nature of three-dimensional (3D) hydrodynamics in the postbounce stalled-shock phase of core-collapse supernovae using 3D general-relativistic hydrodynamic simulations of a 27-M progenitor star with a neutrino leakage/heating scheme. We vary the strength of neutrino heating and find three cases of 3D dynamics: (1) neutrino-driven convection, (2) initially neutrino-driven convection and subsequent development of the standing accretion shock instability (SASI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
161
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(177 citation statements)
references
References 110 publications
(274 reference statements)
15
161
1
Order By: Relevance
“…As some of us found in the parameterized 3D simulations of Abdikamalov et al (2015), lower resolution appears to be more favorable for shock runaway for simulations near the threshold of explosion (cf. Radice et al 2016).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…As some of us found in the parameterized 3D simulations of Abdikamalov et al (2015), lower resolution appears to be more favorable for shock runaway for simulations near the threshold of explosion (cf. Radice et al 2016).…”
Section: Resultsmentioning
confidence: 78%
“…We draw from Woosley et al (2002) the progenitor model s27, which has been studied in a number of previous works (e.g., Müller et al 2012a;Hanke et al 2013;Ott et al 2013;Couch & O'Connor 2014;Abdikamalov et al 2015). In all simulations, we employ the = K 220 MeV 0 variant of the equation of state of Lattimer & Swesty (1991) .…”
Section: Methods and Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic behavior of the accretion shock has not received the attention afforded the SASI and convection, but previous analyses using tracer particles from CHIMERA simulations has shown that much of the matter passing through the shock is directed toward the proto-NS in accretion streams (Chertkow et al 2012;Lentz et al 2012a). We notethat the one or two accretion streams that dominate the accretion in 2D simulations is not characteristic of 3D simulations, which exhibit more numerous but weaker accretion streams Tamborra et al 2013Tamborra et al , 2014Takiwaki et al 2014;Tamborra et al 2014;Abdikamalov et al 2015;Lentz et al 2015).…”
Section: Accretion Streamsmentioning
confidence: 92%
“…In addition to the pre-collapse turbulence, there are post-collapse instabilities in the post-shock inflow toward the neutron star, such as due to heating by neutrinos, and in particular the standing accretion shock instability (SASI; e.g., Blondin et al 2003;Blondin & Mezzacappa 2007;Fernández 2010;Burrows et al 1995;Janka & Mueller 1996;Buras et al 2006a,b;Ott et al 2008;Marek & Janka 2009;Iwakami et al 2014;Abdikamalov et al 2015;Fernández 2015). Most relevant to the jittering jets scenario are the spiral modes of the SASI that carry local angular momentum variations.…”
Section: The Jittering Jets Scenariomentioning
confidence: 99%